Mediation in Teletandem: a locus to experience teacher learning and reflection - MORAES , Ana Luiza Guisso de; SALOMÃO , Ana Cristina Biondo (The ESPecialist, 2022)
This paper presents the results of an investigation on how mediation sessions in the Teletandem Brazil: Foreign languages for all project can be characterized as a locus for foreign language teacher education. At UNESP-Araraquara, mediations have been carried out aiming at fostering participants’ reflections by means of group sessions led by undergraduate and graduate students in languages and linguistics with knowledge and experience in Teletandem. Based on sociocultural theory (VYGOTSKY, 2007), the research focused on the role of mediators as the most competent peers in the scaffolding process and the strategies used to conduct the sessions. The data were collected by audio and video recordings of the mediation sessions and an interview with two mediators from different groups. Through qualitative methodology and an interpretive approach, the analyses show that, in a reasonably comparable way to the structure of a language class, mediators help learners in this telecollaborative context by sequencing themes and activities, using the scaffolding process and following the mediation guidelines for reflective practice. Resonating other research in Teletandem context, the results point to mediation sessions as a collaborative pedagogical practice context for teacher educators to develop teacher learning and reflection.